Development of Moral Intelligence Students Through the Honesty Canteen Program in the Context of Citizenship Education (Case Study in SMAN 8 Bandung) - Faisal Sadam Murron; Kokom Komalasari (MODELING: Jurnal Program Studi PGMI, 2020)
This research is motivated by the lack of facilities for students to do moral action as part or the output of learning Citizenship Education in order to develop their moral intelligence, especially in schools. This study aimed to get information about the development of moral intelligence of learners through honesty canteen program in the context of civic education that includes planning, implementation, advantages and disadvantages of honesty canteen program, the achievement of moral intelligence of learners up its sustainability efforts. The approach used in this study is a qualitative study with the case study method. The process of data collection is done in three ways: observation, interviews and documentation study. Location of the study were used as a case study is SMAN 8 Bandung. The parties are the subject of research is the Civics teachers, principals and students. Based on the results of this study concluded that 1) Increasing the moral intelligence of learners achieved through planning optimal collaboration with stakeholders from government elements that integrate with the concept of honesty canteen program Widyatama school; 2) Moral action will be effective learners developed using honesty canteen media in the context of Civics that engage learners in schools .; 3) Excess honesty canteen program in supporting the development of moral intelligence of learners such as civics laboratory for students in school so that they are able to apply the material Civics that they can be in the classroom, but unfortunately not all the schools are able to understand the role of honesty canteen itself; 4) Through honesty canteen These indicators moral intelligence such as empathy, conscience kotrol self, respect, kindness, tolerance and justice showed a positive development as learners are facilitated to take responsibility for their actions (moral action) unsupervised anyone; 5) In keeping with a program that is good, socialization is needed both to internal and external school by attending various events to keep the existence of this honesty canteen program that moral intelligence that learners can continue to grow.